Pengaruh Content Marketing dan Hedonic Motivation terhadap Impulse Buying di Tiktok pada Mahasiswa STIE Yapis Dompu - Rian Anggriani; Yeyen Suhaety; Firmansyah Firmansyah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze in depth the extent of the influence of content marketing and hedonic motivation on impulse buying in TikTok users, especially STIE Yapis Dompu students. This research illustrates a quantitative approach. The population of this study is all students who actively use the Tiktok Shop at STIE Yapis Dompu, the exact number of which is unknown. The number of samples used was 150. Non-probability sampling technique using the purposive sampling method. The data analysis in this study uses PLS-SEM Analysis. The results of the study showed that content marketing had a positive and significant effect on impulse buying, as evidenced by a t-statistical value of 3,116 > 1.96, and a p-value of 0.002 < 0.05. And hedonic motivation had a positive and significant effect on impulse buying, which was evidenced by a t-statistical value of 6,472 > 1.96, as well as a p-value 0.000 < 0.005. While the content marketing variable for hedonic motivation has a t-statistical value of 5,799 > 1.96, and a p-value of 0.000 < 0.05, content marketing has a positive and significant effect on hedonic motivation in STIE Yapis Dompu students.